2018
DOI: 10.1038/s41598-018-30714-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 375 modulates hyperglycemia-induced enteric glial cell apoptosis and Diabetes-induced gastrointestinal dysfunction by targeting Pdk1 and repressing PI3K/Akt pathway

Abstract: Diabetic neuropathy can damage systemic nervous system, including alteration of enteric nervous system and subsequent gastrointestinal dysfunction. The effect of diabetes on enteric glia cell (EGC) is not clear. We investigated the effect of diabetes and hyperglycemia on EGC, and the role of microRNA375 in modulating EGC survival in vivo and in vitro. Streptozotocin-induced diabetic mice were intraperitoneally injected with microRNA375 inhibitor or its negative control. EGC was transfected with microRNA375 inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…While most of the research focused on the enteric neurons, less attention was directed towards the enteric glial cells (EGCs). Glucose enters the body via the gastrointestinal (GI) tract, and conversely, diabetes-induced GI dysfunction is related to increased apoptosis of EGC in the myenteric plexus ( 211 ). On the other hand, the gut clock synchronized by food intake ( 27 , 212 ) regulates the expression of brush border disaccharidases and glucose absorption to the habitual feeding period ( 168 ).…”
Section: Integration Of Glucose Homeostasis By Astrocyte Clocks and Cmentioning
confidence: 99%
“…While most of the research focused on the enteric neurons, less attention was directed towards the enteric glial cells (EGCs). Glucose enters the body via the gastrointestinal (GI) tract, and conversely, diabetes-induced GI dysfunction is related to increased apoptosis of EGC in the myenteric plexus ( 211 ). On the other hand, the gut clock synchronized by food intake ( 27 , 212 ) regulates the expression of brush border disaccharidases and glucose absorption to the habitual feeding period ( 168 ).…”
Section: Integration Of Glucose Homeostasis By Astrocyte Clocks and Cmentioning
confidence: 99%
“…Similarly, diabetes can reduce the number of enteric nerves, and restoration of PI3K signaling can lead to regeneration of lost enteric neurons [59], which may alleviate gastrointestinal symptoms in diabetic patients. More recently, sustaining PI3K signaling has been shown to improve gastrointestinal function in diabetes, also by facilitating survival of other cells connected with nerve fibers, such as enteric glia [60].…”
Section: Pi3k and Diabetic Neuropathy And Encephalopathymentioning
confidence: 99%
“…Furthermore, it has been observed that metabolic diseases e.g., diabetes and obesity also present with increased ratio of Firmicutes to Bacteriodetes (Conlon and Bird, 2014; Johnson et al, 2017). Studies concerning the mechanisms of these gastrointestinal diseases have found that change of EGC phenotype from homeostatic to pathogenic is a characteristic of these diseases (Cabarrocas et al, 2003; Linan-Rico et al, 2016; Chen et al, 2018). A study by Wang et al reported a significantly increased expression of glial fibrillary acidic protein (GFAP), Tyrosine receptor kinase B and Substance P in the colon of IBS patients with a correlated increase in intestinal inflammation (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%